2017
DOI: 10.1371/journal.pone.0176730
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with help-seeking behaviour among individuals with major depression: A systematic review

Abstract: Psychological models can help to understand why many people suffering from major depression do not seek help. Using the ‘Behavioral Model of Health Services Use’, this study systematically reviewed the literature on the characteristics associated with help-seeking behaviour in adults with major depression. Articles were identified by systematically searching the MEDLINE, EMBASE and PsycInfo databases and relevant reference lists. Observational studies investigating the associations between individual or contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
188
10
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(228 citation statements)
references
References 68 publications
24
188
10
6
Order By: Relevance
“…Intriguingly, the gender differences often reported in studies from high-income countries were not replicated in this setting, and we found the opposite association between marital status and treatment-seeking that which is typically reported elsewhere (6,7,64). This demonstrates the importance of local data in identifying vulnerable groups for service planning, and provides suggestive evidence that processes believed to inhibit treatment-seeking in other cultural contextssuch as masculine ideals of self-sufficiency (65, 66) -may not apply in the same way to Indian populations.…”
Section: Who Seeks Health Care For Depression Symptoms?contrasting
confidence: 88%
“…Intriguingly, the gender differences often reported in studies from high-income countries were not replicated in this setting, and we found the opposite association between marital status and treatment-seeking that which is typically reported elsewhere (6,7,64). This demonstrates the importance of local data in identifying vulnerable groups for service planning, and provides suggestive evidence that processes believed to inhibit treatment-seeking in other cultural contextssuch as masculine ideals of self-sufficiency (65, 66) -may not apply in the same way to Indian populations.…”
Section: Who Seeks Health Care For Depression Symptoms?contrasting
confidence: 88%
“…Based on 30 days before the emergency department visit.b For mental disorder variables, the reference group consists of treatment episodes without the disorder.Any mental diagnosis recognized during index emergency department visit for deliberate self-harm. Moreover, the only variable associated with lower likelihood of follow-up mental health care was male gender (ARR = 0.82, 99% CI = 0.71-0.94), which is consistent with research demonstrating lower help-seeking behavior in men 66,67. Prior US research shows that roughly 50% of younger ED patients discharged to the community following self-harm proceed to followup on referrals to outpatient mental health services 26,28,62.…”
supporting
confidence: 77%
“…65 Moreover, the only variable associated with lower likelihood of follow-up mental health care was male gender (ARR = 0.82, 99% CI = 0.71-0.94), which is consistent with research demonstrating lower help-seeking behavior in men. 66,67 Because active contact and mental health care following self-harm events reduce repeated selfharm 68,69 and suicide mortality, 10,11 guidelines in the management of self-harm emphasize the importance of rapid referral and outreach to ensure receipt of mental health care. 33,34,[70][71][72] This study has several potential limitations.…”
Section: Outpatient Mental Health Carementioning
confidence: 99%
“…For example, Gulliver, Griffiths, and Christensen (2010) conducted a systematic review on barriers to mental health help-seeking and found that among adolescents, factors inhibiting help-seeking included, though are not limited to, perceived stigma, low mental health literacy, and embarrassment. Magaard et al (2017) found that feeling uncomfortable asking for help is associated with lower likelihood for seeking assistance. In addition to these contextual factors, scholars have underscored the importance of considering the cognitive processes of individuals with elevated depressive symptomatology (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…Although depression is treatable, there is a disparity between the number of individuals who need treatment and the number of individuals who seek treatment; only 20 per cent of individuals with moderate, and 35 per cent of those with severe, depressive symptomatology sought professional help for their symptoms in the year prior to being surveyed (Pratt & Brody, 2014). In addition, men, young adults, elderly persons, and those with lower education status are among the least likely to seek help (Magaard, Seeralan, Schulz, & Br€ utt, 2017). Research that focuses on bridging this gap and identifying additional risk factors is important, as failing to take action and subsequently allowing symptoms to remain untreated for extended periods of time may worsen depressive symptomatology and ultimately result in suicide (WHO, 2016).…”
Section: Introductionmentioning
confidence: 99%